2022
DOI: 10.22159/ijpps.2022v14i11.46070
|View full text |Cite
|
Sign up to set email alerts
|

To Evaluate the Safety and Efficacy of Amlodipine and Chlorthalidone in Combination With Telmisartan in Hypertensive Patients Attending Tertiary Care Centre, Telangana

Abstract: Objective: The main objective of this study is to evaluate and compare the effects of both treatments on systolic and diastolic blood pressure in 4th, and 8th weeks with baseline Methods: A prospective, comparative, Open-label, and parallel-group clinical study was conducted in out patient's department of general medicine at Osmania general hospital. 120 patients were randomly allocated into 2 groups. Group 1 with 60 patients received Tab: Telmisartan 40 mg+Amlodipine 5 mg once daily, and Group 2 with 60 patie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 12 publications
0
4
0
Order By: Relevance
“…According to Sharma et al, integrating spiritual healing traditions and medical practitioners at the local level may aid in early referral and the beginning of appropriate therapy 31 .Most of our surveyees believed in surgical treatment for epilepsy, similar to a work by Santhosh NS 7 . Nonetheless, in other investigations, the majority were unaware of the same 13,18,27,30 .…”
Section: Discussionmentioning
confidence: 86%
See 2 more Smart Citations
“…According to Sharma et al, integrating spiritual healing traditions and medical practitioners at the local level may aid in early referral and the beginning of appropriate therapy 31 .Most of our surveyees believed in surgical treatment for epilepsy, similar to a work by Santhosh NS 7 . Nonetheless, in other investigations, the majority were unaware of the same 13,18,27,30 .…”
Section: Discussionmentioning
confidence: 86%
“…Our EP/CG had good KAP related to the right dose, brand, and withdrawal of the therapy and its consequences, akin to a study by Shaju et al 17,26 .Analogous to our finding, 58.7% of science graduates in Karnataka agreed on the lifethreatening aspects of discontinuing AEDs, but contrary to our study, 59.3% believed AED discontinuation was impos-sible even after a three-year seizure-free interval 12 .This lack of cognizance could be attributed to non-epileptic population involved in that study. Similar to previous explorations, our subjects also maintained a seizure diary and adhered to the doctor's advice (reminders) to avoid missing doses 18,19 .Our study identified positive awareness and attitudes towards TDM, but in a Kochi-based survey, most individuals were ignorant 17 .Half of the answerers felt AEDs were safe during pregnancy, similar to a review that has stated the need for individualizing the therapy based on the risk and benefit 36 .On the whole, the KAP of EP/CG was better than that of nonepileptic individuals, in line with other studies 2,19 .…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…Uncontrolled hypertension is a significant risk factor for cardiovascular, renal and endocrine disorders. Long-acting dihydropyridine calcium channel blockers (CCBs) are used as firstline agents for hypertension, either as a monotherapy or in combination with other antihypertensive agents [11,12]. Cilnidipine is a unique and effective 1, 4 dihydropyridine CCB, which blocks both L and N-type calcium channels.…”
Section: Introductionmentioning
confidence: 99%